REKONSTRUKSI PRAKTIK PEMBELAJARAN MELALUI PEDAGOGI KRITIS PAULO FREIRE DALAM MENGHADAPI TRANSFORMASI PENDIDIKAN ABAD KE-21 - Kurniawati, Nia; Nina, Neng; S, Yetti; Suwardi, Inas Wies; Suryani; Komara, Endang; Sobari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical pedagogy, developed by Paulo Freire, is an educational paradigm that positions learners as active participants in the learning process through dialogue, reflection, and action aimed at fostering critical awareness of social realities. This study aims to describe the concept of Paulo Freire's critical pedagogy and analyze its relevance to the development of learning models in the era of digital transformation. The study employed a library research method using a qualitative descriptive approach. Data were collected from scholarly sources, including books, national and international peer-reviewed journal articles published between 2019 and 2025, and policy documents related to critical pedagogy and twenty-first-century learning models. Data analysis was conducted through data reduction, data display, and conclusion drawing, with credibility established through source triangulation. The findings indicate that critical pedagogy rejects banking education, which positions students as passive recipients of knowledge. Instead, Freire proposes dialogical education, problem-posing education, and the development of critical consciousness (conscientization) through reflection and action (praxis). These principles align with twenty-first-century learning demands emphasizing critical thinking, creativity, communication, and collaboration (4Cs), and are consistent with contemporary learning models such as Problem Based Learning, Project Based Learning, and Learning Management Systems in technology-based instruction. Implementation has the potential to enhance students' active participation, problem-solving abilities, and social awareness, although challenges include conventional teaching culture, limited teacher competence, dense curricula, and assessment systems focused primarily on academic outcomes.